First-Time Fathers’ Experiences in Antenatal Care - Reyes, Lady Marianne; Abainza, Jewelrie Mae; Hernandez, Shaina Claire; Urbano, Anne Emmanuelle; Belista, Ian Justine; Lajara, Vivian; Quintana, Marc Lester (Journal of Interdisciplinary Perspectives, 2025)
First-time fathers' involvement in the antenatal care of their pregnant partners is recognized as important for improving maternal and child health. However, engaging in this process can be challenging as they encounter different barriers. Their involvement in decision-making for seeking health care and obtaining health facilities can influence maternal outcomes, possibly affecting the maternal death rate. This study aims to provide information on what programs can be implemented to encourage more fathers to participate and support the antenatal care of their pregnant partners by exploring their lived experiences. This study aligns with Sustainable Development Goal 3 and 5, which focus on good health, well-being, and gender equality. The researchers employed a qualitative research design using a hermeneutic phenomenological approach. Data was gathered through self-made questionnaires from ten participants selected through snowball sampling, targeting first-time fathers aged 18 and above whose partner is currently pregnant and residing in the 3rd District of Laguna. The thematic and interpretative phenomenological analysis identified the major themes and sub-themes. The findings revealed four major themes: anticipating parenthood, embracing new roles, mutual support in pregnancy, and active engagement in prenatal care that exhibit the first-time fathers’ state of preparedness and antenatal involvement during the pregnancy of their partners. Their willingness to be part of the antenatal care of their pregnant partners was seen. For them, antenatal care is a shared responsibility, not just for women. They demonstrated positive behavior toward antenatal care as they have a good perception of it. It is recommended to implement programs for first-time fathers that focus on pregnancy, helping reduce anxiety and enhance understanding of their responsibilities.